Silencing of LRRFIP1 reverses the epithelial–mesenchymal transition via inhibition of the Wnt/β-catenin signaling pathway. Issue 1 (28th August 2015) - Douchi, Daisuke; Ohtsuka, Hideo; Ariake, Kyohei; Masuda, Kunihiro; Kawasaki, Shuhei; Kawaguchi, Kei; Fukase, Koji; Oikawa, Masaya; Motoi, Fuyuhiko; Naitoh, Takeshi; Katayose, Yu; Egawa, Shinichi; et al.
Highlights The role of LRRFIP1 in the EMT and invasion of carcinoma cells was investigated. Repression of LRRFIP1 caused reversal of EMT and inhibited migration and invasion. Silencing of LRRFIP1 regulated phosphorylation and nuclear localization of β-catenin. β-catenin expressed on the membrane was increased in LRRFIP1 silenced cancer cells.